CONSUMER PROTECTION: THE PHENOMENON OF CONSIDERATION SERVICES FOR PURCHASE OF GOODS - Aswari, Aan; Jannah, Miftahul; Fauzi, Fathu Rizqi; Aisyah, Nur (JCH (Jurnal Cendekia Hukum), 2024)
The urgency of this research is to understand the unique impact of each legal action, enabling the improvement of the legal system and for the sake of legal justice. The analysis of legal relationships in the sale and purchase agreement of online entrustment services is important to identify the rights and obligations of each party, so as to ensure consumer protection, and serve as a basis for measuring the success of the e-commerce regulatory system. The purpose of this research is to analyze legal protection for consumers and detect the laws used by the parties in online goods purchase and sale agreements. This research uses empirical legal research methods. The results show that the legal protection of consumers in the sale and purchase agreement of online entrustment services is entitled to compensation and replacement if the goods received are not in accordance with the agreement. Personal shopper business actors have provided legal protection with the fulfillment of consumer rights. The legal relationship that occurs in the business of buying and selling services can be categorized as buying and selling because the essential elements are fulfilled, namely the agreement on goods and prices. The research aims to ensure that concrete action is taken, so far there are very few legal rules that specifically discuss personal shopper agreements, this is held in order to guarantee the rights and obligations and protection. For business actors, buying and selling services should in writing contain the obligations and rights of each, including the mechanism in the sale and purchase agreement and the responsibilities of personal shopper business actors.